Chitosan Xylotrupes gideon encapsulated lemongrass leaf ethanol extract reduce H2O2‐induced oxidative stress in human dermal fibroblast - Komariah Komariah; Pretty Trisfilha; Rahman Wahyudi; Nada Erica; Didi Nugroho; Yessy Ariesanti; Sarat Kumar Swain (Indonesian Journal of Biotechnology, 2023)
During phagocytosis, phagocyte cells discharge reactive oxygen species referred to as respiratory bursts, inducing a rise in pro‐oxidants and subjecting the cell to oxidative stress. Such stress is a biological mechanism related to an imbalance in pro‐oxidant/antioxidant homeostasis, which generates toxic reactive oxygen. Encapsulation is a coating process to improve the stability of bioactive compounds from lemongrass extract. Therefore, this study aims to determine the encapsulation activity of lemongrass leaf extract with chitosan X. gideon (LEChXg) to reduce the oxidative stress of fibroblasts. The research used the human dermal fibroblast (HDF) cell line, comprising negative and positive controls and use of LEChXg 100, 200, 300, 400, and 500 µg/mL. HDF cell migration was evaluated by employing the scratch wound healing method and the wound closure was oberseved at 0, 2, 4, 6, and 24 h intervals. The cell proliferation was observed at 24, 48, and 72 h using CCK‐8 at a 450 nm wavelength. The results showed that the observations at 0, 2, and 4 h did not demonstrate any significant difference on the cell migration (p > 0.05) among the groups. However, the wound closure at 4 and 6 h showed a significant difference (p < 0.05) with LEChXg 300 µg/mL. Despite the lack of any significant variation observed up to 24 h, fibroblast subjected to the stressor did not achieve complete closure. The groups treated with LEChXg were more stable in maintaining fibroblast proliferation up to the end of the observation than those with stressors at 24, 48, and 72 h. Fibroblast induced with a stressor was also more stable in maintaining migration and proliferation in groups receiving LEChXg 300 µg/mL.